PENGEMBANGAN METODE PENENTUAN INDEKS LUAS DAUN PADA PENUTUP LAHAN HUTAN DARI DATA SATELIT PENGINDERAAN JAUH SPOT-2 - Suwarsono, Suwarsono; Arief, Muchlisin; Hidayat, Hidayat; Sulma, Sayidah; Suryo H, Nanik; Sulyantoro, Heri; Setiawan, Kuncoro Teguh (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2011)
It is necessary to develop the methods of Leaf Area Index (LAI) estimation based on satellite remote sensing data as first step to study the carbon storage and carbon emission which affect to global climate change. Direct measurements of Leaf Area Index in the field are expensive, take a long time, and so inefficient. The application of remote sensing data may gives an appropriate solution for Leaf Area Index estimation by more efficient and effective. Objective of the research is to develop the method of Leaf Area Index estimation by using remote sensing data. The method of Leaf Area Index estimation will be developed by using the reference method taken from back up algorithm of the Algorithm Theoretical Basis Document (ATBD) MOD15. The research will try to develop the model and applicate it for another remote sensing data, especially those of acquired or distributed by Indonesian National Institute of Aeronautics and Space (LAPAN) such as SPOT-2. Results of the research show that the LAI based on MOD 15 has low correlation with the measured LAI, but the measured LAI has good correlation with NDVI from SPOT-2 for forest area.